2014
DOI: 10.1039/c4cp00867g
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of the electronic structure of some stable nitroxyl radicals using variable energy photoelectron spectroscopy

Abstract: The photoionization of three stable nitroxyl radicals has been studied in the valence and core regions using synchrotron radiation. We observed different variations of the relative band intensities with the photon energy for two pyrrolidine nitroxyls (nitroxyl8 and nitroxyl9) in the valence ionization region. This is due to strong intramolecular interactions between the amide substituent and the ring π-orbital when present. In the core ionization region we observed chemical shifts which were consistent with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(45 citation statements)
references
References 34 publications
2
43
0
Order By: Relevance
“…Thus, there is need for further development of informative characterization techniques that could be applied to stable radicals. X-ray absorption near-edge structure (XANES) spectroscopy and related techniques are particularly promising in this regard, as has been demonstrated in earlier studies (see, for instance, refs ).…”
Section: Introductionmentioning
confidence: 94%
“…Thus, there is need for further development of informative characterization techniques that could be applied to stable radicals. X-ray absorption near-edge structure (XANES) spectroscopy and related techniques are particularly promising in this regard, as has been demonstrated in earlier studies (see, for instance, refs ).…”
Section: Introductionmentioning
confidence: 94%
“…Photoionization of TEMPO has been thoroughly studied, experimentally and theoretically, by Ljubić, Novak, and co-workers using UV/Vis and X-ray photoelectron spectroscopy. [99][100][101][102] These studies demonstrated a good agreement between the experimental photoelectron spectra and theoretical spectra simulated using density functional theory (DFT). However, electron attachment to TEMPO has not been investigated as extensively as its photoionization.…”
Section: B Tempo Radicalmentioning
confidence: 55%
“…Differently, the observed acrylamide binding energies are greater (O(1s) +0.2 eV, N(1s) +0.2 eV, C1(1s) +0.4 eV) than those of N-methylacetamide [39]. In addition, in the case of 3-carbamoyl-2,2,5,5-tetramethyl-3-pyrrolin-1-oxyl (C 9 H 15 N 2 O 2 ) that for our purposes can be described as an acrylamide frame embedded in cyclic nitroxyl radical through the C=C bond, the binding energies of acrylamide are blue shifted: O(1s) +0.32 eV, N(1s) +0.07 eV, C1(1s) +0.16 eV and C2/C3(1s) +0.33 [40]. Comparison with pyridin-2-one, where the amide frame is embedded in a conjugate ring system, shows that the O(1s) binding energy of acrylamide is +0.6 eV greater, whereas the N(1s) binding energies is −0.4 eV smaller [41].…”
Section: Xpsmentioning
confidence: 95%